Implementation of Arabic Animation Videos in Maharah Istima Learning Based on Behavioristic Theory - Arista, Dian; Al Faruqi, Mhd Ibnu Hanan; Fitriani, Laili; Aziz, Abdul (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2025)
This study aims to implement Arabic animation videos in learning Maharah Istima' (listening skills) based on behavioristic theory. The background of this research is based on the challenges in learning Arabic, especially in improving students' listening skills which are often considered less interesting and monotonous. Behavioristic theory was chosen because it emphasizes habit formation through repetition and reinforcement, which is considered effective in language learning. In addition, there are three reinforcements in behavioristic theory that are stimuli to get a good response from students, namely positive, negative, and punishment reinforcement. The research method used is a descriptive qualitative research method. The participants in this study are students in class PBA A UIN Maulana Malik Ibrahim Malang. Data was collected through interviews and observation of student activities during learning. The data analysis technique used is the Miles & Huberman interactive analysis technique with three stages, namely data reduction, data presentation, and conclusion drawn. The results of the study show that the use of Arabic animation videos in Istima' learning can help students increase motivation and understanding. The behavioristic theory used during the learning process can make students focus in class. The implication of this study is the importance of integrating technology and creative media in learning Arabic, especially in developing more interactive and interesting learning methods based on relevant learning theories. This research contributes to the development of innovative Arabic language learning strategies oriented towards improving students' skills.